2019
DOI: 10.18257/raccefyn.844
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización del agente causante de la deformación de los frutos de la uva (Vitis vinifera L.) var. Red Globe en La Unión, Valle del Cauca, Colombia

Abstract: En años recientes una enfermedad caracterizada por la necrosis y el hundimiento de la epidermis de las bayas de la vid (Vitis viinifera L.) se ha venido presentando en la variedad Red Globe, cultivada en predios vitícolas del municipio de La Unión, Valle del Cauca, lo que ha resultado en pérdidas de rendimiento y calidad. Para determinar la etiología de la enfermedad, se recolectaron y procesaron frutos que mostraban los signos típicos de decoloración y posterior necrosis. Con mayor prevalencia se encontró un … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The pathogenicity of grapes in physiological stage 79 (Lorenz, et al, 1994) was subsequently tested and Koch's postulates were verified. Later, we determined that it belonged to the C. gloesporioides species complex using molecular tools (López-Zapata, et al, 2019) and with it, we carried out the sensitivity tests of the four fungicides.…”
Section: Fungal Isolatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathogenicity of grapes in physiological stage 79 (Lorenz, et al, 1994) was subsequently tested and Koch's postulates were verified. Later, we determined that it belonged to the C. gloesporioides species complex using molecular tools (López-Zapata, et al, 2019) and with it, we carried out the sensitivity tests of the four fungicides.…”
Section: Fungal Isolatesmentioning
confidence: 99%
“…The disease occurs mainly on ripe fruits (Lei, et al, 2016), although infections are also present in developing fruits (Gil, et al, 2002;Jiang, et al, 2014) as has been observed at La Union vineyards (López-Zapata, et al, 2019). Grapes infected with Colletotrichum present lesions characterized by dark circular spots on the epidermis resulting in total damage to the berries that are then covered with masses of salmon-colored spores (Shiraishi, et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation